ANALISIS KEMAMPUAN DAN KEMAUAN MEMBAYAR TARIF PADA PENGGUNA JASA MODA TRANSPORTASI KAPAL LAUT (Studi Kasus : Rute Ternate-Sanana) - Dahlia Canra; Arbain Tata; Ichsan Rauf (Fakultas Teknik, Universitas Wiraraja, 2022)
The mode of transportation in this case is the ocean liner is an alternative transportation that is most often chosen by the public in traveling, one of which is for the Ternate-Sanana route. For this type of transportation is relatively lancer and almost every day available. There are 3 (three) ships operating in a week. One of the important factors in the management of sea transportation services is tariffs. This is the reason people use this mode of transportation, because it is considered quite affordable compared to other modes of transportation. Therefore, this study was conducted to find out Ability To Pay (ATP) and Willingness To Pay (WTP) users of sea ship transportation services with the Ternate-Sanana route. Where later it can be a consideration in evaluating the appropriate tariff. From the data that has been processed, the value of Ability To Pay (ATP) is Rp 471,722,- and the value of Willingness To Pay (WTP) is Rp 229,100,-.